2017
DOI: 10.1002/asi.23781
|View full text |Cite
|
Sign up to set email alerts
|

Developments in research data management in academic libraries: Towards an understanding of research data service maturity

Abstract: New Zealand, and the UK. The results indicate that libraries have provided leadership in RDM, particularly in advocacy and policy development. Service development is still limited, focused especially on advisory and consultancy services (such as data management planning support and data-related training), rather than technical services (such as provision of a data catalog, and curation of active data). Data curation skills development is underway in libraries, but skills and capabilities are not consistently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
176
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(191 citation statements)
references
References 33 publications
4
176
0
11
Order By: Relevance
“…The results of this study were in keeping with past studies in other geographic regions, which similarly found that libraries are likely to focus on the advisory rather than technical aspects of RDS (Cox, Kennan, Lyon, & Pinfield, 2017). RDS implementation also presents many challenges to academic libraries, and future research is vital to determining how RDS develops overtime and how librarians adapt to these challenges.…”
Section: Commentarysupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study were in keeping with past studies in other geographic regions, which similarly found that libraries are likely to focus on the advisory rather than technical aspects of RDS (Cox, Kennan, Lyon, & Pinfield, 2017). RDS implementation also presents many challenges to academic libraries, and future research is vital to determining how RDS develops overtime and how librarians adapt to these challenges.…”
Section: Commentarysupporting
confidence: 84%
“…The current literature on RDS in academic libraries focuses primarily on providing benchmarks for the current state of RDS as well as librarians' plans for future services. Past surveys have been geographic, including studies of RDS in North America, the UK, and Australasia (Tenopir et al, 2015;Cox, Kennan, Lyon, & Pinfield, 2017). This study builds on that literature by extending this inquiry to a European context.…”
Section: Commentarymentioning
confidence: 93%
“…Widespread use of the term implies a common set of services (e.g., data management plan consultations, data discovery and citation, and data information literacy instruction), which is rather misleading. Libraries are still in the process of defining the boundaries of research data services (Cox, Kennan, Lyon, & Pinfield, 2017;Bryant, Lavoie, & Malpas, 2017). The context for RDS programs-their organizational placement, degree of centralization, and which library staff provide them-is highly heterogeneous (Fearon, Gunia, Lake, Pralle, & Sallans, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The context for RDS programs-their organizational placement, degree of centralization, and which library staff provide them-is highly heterogeneous (Fearon, Gunia, Lake, Pralle, & Sallans, 2013). These services may also be composed of traditional library functions paired with new services (Cox et al, 2017). Often, RDS are not feasible without strong partnerships between offices of research and IT services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation